The Authority of Police in Implementation of Restorative Justice in Framework of Enforcement of Criminal Actions in Indonesia - Arif Khoirul Umam; Sri Endah Wahyuningsih; Achmad Sulchan (Universitas Islam Sultan Agung, 2022)
This study aims to identify and examine the authority of the Police in the application of restorative justice in the context of law enforcement of criminal acts in Indonesia. This study uses a normative juridical approach with descriptive analysis. The data used was secondary data, which was then analyzed qualitatively. Based on the research, it is concluded that the authority of the Police in the application of restorative justice in the context of law enforcement of criminal acts in Indonesia is based on the provisions of Article 16 paragraph (1) letter l, Article 16 paragraph (2) and Article 18 of Act No. 2 of 2002 which is known as Police discretionary terms. Based on this authority, the Police may act on the basis of their own discretion and judgment in carrying out the functions of the Police. To ensure uniformity in the implementation of restorative justice within the Police, the Republic of Indonesia National Police (Polri) Regulation Number 8 of 2021 concerning Handling of Crimes Based on Restorative Justice was issued. The handling of criminal acts based on restorative justice by the Police based on Police Regulation Number 8 of 2021 must meet general and special requirements. The general requirements apply to the activities of carrying out the criminal investigation, investigation, or investigation functions, while the special requirements only apply to criminal acts based on restorative justice in investigative or investigative activities. Besides that,